In Silico Screening of Medicinal Plant-Derived Compounds Against Spodoptera litura: In Silico Screening of Medicinal Plant-Derived Compounds Against Spodoptera litura - Jiang, Yingying; Kuppusamy Alagesan, Paari (Journal of Tropical Life Science, 2025)
Spodoptera litura (Lepidoptera: Noctuidae) is a major agricultural pest in the Asia-Pacific region, causing significant crop damage. Current pest control strategies heavily rely on chemical pesticides, leading to environmental concerns and rapid resistance development. Molecular docking and molecular dynamics studies were used to investigate bio-compounds from three medicinal plants - Vitex negundo, Artemisia nilagirica, and Portulaca oleracea—as potential eco-friendly pest management alternatives. Gas chromatography-mass spectrometry (GC-MS) analysis identified 28 phytochemicals, of which 14 conformed to Lipinski’s Rule of Five, which were selected as ligands. Molecular docking simulations were conducted to evaluate ligand interactions with four key target proteins in Spodoptera litura: acetylcholinesterase (AChE), carboxylesterase (CES), ecdysone receptor (EcR) and juvenile hormone (JH). Among the tested compounds, oxalic acid, 6-ethyloct-3-yl hexyl ester, and (11Z)-13-methyl-11-tetradecenyl acetate exhibited the highest binding affinities (-8.4 to -6.5 kcal/mol), suggesting their potential as inhibitory agents. Normal mode analysis (NMA) revealed low eigenvalues of the complexes, ranging from 9.699226×10-5 to 3.071589×10-4, indicating flexibility and requiring minimal energy for conformational changes. Deformability was highest in hinge regions, while variance analysis confirmed inverse proportionality across the complexes. The B-factor graph highlighted stable mobility and the root mean square (RMS) of the 3D conformer structures. Elastic network graphs displayed residue interactions as dots, with darker grey areas signifying greater stiffness. ADME/T analysis showed that these compounds possess favorable pharmacokinetic properties, including efficient absorption and metabolism, while exhibiting no significant risks of mutagenicity or cardiotoxicity. These findings further support the suitability of Oxalic acid, 6-ethyloct-3-yl hexyl ester, and (11Z)-13-Methyl-11-tetradecenyl acetate as promising candidates for advancing sustainable and eco-friendly pest management approaches. Furthermore, the potential of identified plant-derived compounds as novel biopesticides contributes to sustainable and environmentally responsible pest management strategies.